Clinical detection of "extremely low‐risk" follicular thyroid carcinoma: A population‐based study of 7304 patients. Issue 4 (15th June 2022) - Le, Minh‐Khang; Odate, Toru; Vuong, Huy Gia; Mochizuki, Kunio; Kondo, Tetsuo
Abstract: Background: Previous studies have not been consistent in the risk of metastasis in follicular thyroid carcinoma (FTC). Therefore, we conducted a large population study to stratify the risk of distant metastasis in FTC patients using only clinical parameters. Methods: We extracted FTC patients from The Surveillance, Epidemiology, and End Results (SEER) database and divided them into training and validation cohorts. Results: The two cohorts consisted of 4913 and 2391 patients, respectively. We developed a nomogram and risk table based on a logistic regression model using algorithm‐selected variables. Receiver Operating Characteristic (ROC) analyses showed high discriminatory power in the training and validation cohorts (Area under the curve [AUC] of 0.85 and 0.84, respectively). Extremely low, low, intermediate, and high‐risk groups had 0.3%, 1%, 3.5%, and 16.7% risk of distant metastasis, respectively. Conclusions: Our risk scoring table can separates patients into four risk groups and efficiently detect patients with almost no risk of metastasis. Abstract : We collected 7, 304 FTC patients to establish a risk table for detecting FTC patients with different metastatic risks. We found that the risk table can efficiently detect patients with almost no risk of metastasis, which can provide additional information along with screening imaging techniques.